2022
DOI: 10.1039/d1nr07708b
|View full text |Cite
|
Sign up to set email alerts
|

Dissolving microneedle-encapsulated drug-loaded nanoparticles and recombinant humanized collagen type III for the treatment of chronic wound via anti-inflammation and enhanced cell proliferation and angiogenesis

Abstract: The first recombinant humanized collagen type III (rhCol III) and naproxen (Nap) loaded poly(lactic-co-glycolic acid) (PLGA) nanoparticles incorporated hyaluronic acid (HA) microneedle (MN) was fabricated for diabetic chronic wounds therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…It can also deliver effective drugs in order according to the wound conditions. It is worth mentioning that rh col III is synthesized based on Gly483-Pro512 fragment and has strong cell adhesion (Long et al, 2022).…”
Section: Internal Environment Responsivenessmentioning
confidence: 99%
“…It can also deliver effective drugs in order according to the wound conditions. It is worth mentioning that rh col III is synthesized based on Gly483-Pro512 fragment and has strong cell adhesion (Long et al, 2022).…”
Section: Internal Environment Responsivenessmentioning
confidence: 99%
“…CD31 is a transmembrane protein expressed in early angiogenesis, indicating neovascularization, while α-SMA is a cytoplasmic protein expressed in later angiogenesis, indicating the maturation of vascular smooth muscle cells [ 34 ]. The vascular network plays a key role in the repair of full-thickness skin due to its function of transporting nutrients, oxygen and immune cells into the wound area [ 26 ]. CD31/α-SMA immunofluorescence was performed on the wound tissues at 7 and 14 days.…”
Section: Resultsmentioning
confidence: 99%
“…Recombinant collagen is a novel biomaterial manufactured by synthetic biology techniques and is a candidate material for various medical applications [ 25 ]. Type III collagen is a major component of the extracellular matrix in internal organs and skin in adults [ 26 ]. The recombinant human collagen III protein (rhCol III) is the product of a re-optimized design gene sequence based on the characteristics and main functional domains of human collagen.…”
Section: Introductionmentioning
confidence: 99%
“…67 To suppress persistent inflammation and ameliorate adverse tissue remodeling, Wang et al prepared a HA MN loaded with recombinant humanized collagen type III (rhCol III) and naproxen (Nap) for the treatment of diabetic chronic wounds. 68 To enable the sustained release of the drug to the wound site for a long time, they encapsulated Nap in poly(lactic-co-glycolic…”
Section: Mnsmentioning
confidence: 99%
“…67 To suppress persistent inflammation and ameliorate adverse tissue remodeling, Wang et al prepared a HA MN loaded with recombinant humanized collagen type III (rhCol III) and naproxen (Nap) for the treatment of diabetic chronic wounds. 68 To enable the sustained release of the drug to the wound site for a long time, they encapsulated Nap in poly(lactic- co -glycolic acid) nanoparticles, thereby reducing frequent dressing changes, avoiding the sudden release of the drug and alleviating inflammatory response. Results of the animal experiment suggested that the prepared MNs could accelerate diabetic chronic wound healing by reducing the inflammatory response and enhancing angiogenesis and collagen deposition.…”
Section: Categories Of Multifunctional Wound Dressingsmentioning
confidence: 99%